Antibiotic dispensing without a prescription across community pharmacies: A simulated patient study - Thu Anh Do; Phuong Bao Quan; Thy Tran-Bao Le; Tuyen Thanh Du; Suong Thi-Thanh Duong; Kim Thai-Thien Nguyen; Khoi Ngoc Nguyen; Hoa Quoc Nguyen (Exploratory Research in Clinical and Social Pharmacy)
Objectives: This study aimed to investigate the proportion of antibiotics dispensed, counseling content, and factors associated with antibiotic dispensing for patients with common cold symptoms among community pharmacists (CPs) in Ho Chi Minh City (HCMC). Methods: A cross-sectional study was conducted from January to June 2023 using a simulated patient (SP) method. A total of 352 community pharmacies across 24 districts in HCMC were randomly selected. The SP provided complaints including having fever, sore throat, cough, swallowing difficulty, stuffy nose and asked for treatment. Bayesian Model Averaging was undertaken to determine the factors associated with antibiotic dispensing practices. Results: Of 352 enrolled pharmacies, the proportions of antibiotics suggested and eventually dispensed by CPs were 86.4 % and 83.0 %, respectively. Antipyretics, corticosteroids, and cough medicines were also frequently dispensed (94.9 %, 90.1 %, and 85.8 %, respectively). Only 1.7 % of the CPs provided reasons to take antibiotics, and 8.8 % advised to take the full course of antibiotics. While 80.1 % of CPs counseled on the dosage of medications dispensed, 1.7 % provided information regarding potential drug adverse reactions. CPs at chain pharmacies and in urban areas were less likely to dispense antibiotics without a prescription than their peers at independent pharmacies (OR = 0.32; 95 % CI: 0.17–0.59) and in rural areas (OR = 0.53, 95 % CI: 0.29–0.97). Conclusion: A high proportion of CPs dispensing antibiotics without a prescription along with inadequate counseling content, especially at independent pharmacies and in rural areas was recorded. These issues hightlight the need to improve CPs' knowledge regarding antibiotic resistance and appropriate antibiotic use.